Analisis Efektivitas Penerapan Green Accounting - Niken Maulydia Muttaqin; Lilis Lasmini; Dhea Imroatul Fatihah (Akuisisi : Jurnal Akuntansi, 2026)
The research intends to examine the effectiveness of implementing green accounting at Karawang Islamic Hospital, and how costs related to the environment are trated. The project utilizes a descriptive qualitative method. Data gathering involved interviewing and examining primary data including environmental cost budget realization reports related to environmental costs. The results found that Karawang Islamic Hospital has reported financial impacts but has not recorded them separately, this classification of environmental costs is included in administrative and general costs.